Порівняння хромосом 5-ї гомеологічної групи аврори та авротики з використанням специфічних мікросателітів - Єфіменко, Т.С.; Федак, Ю.; Антонюк, М.З.; Терновська, Т.К. (Фактори експериментальної еволюції організмів, 2014)
Aims. Determine the possibility to use microsatellite loci specific to chromosomes of homeologous group 5-th for distinction of Aurora (AABBDD) and Aurotica (AABBTT) chromosomes. Methods.PCR with primers specific to SSR loci mapped at chromosomes 5А, 5В, and 5D. Results. From 112 studied SSR loci specific to 3 homeologous chromosomes of group 5, 13 loci were selected as diagnostically valuable for identification of 5T chromosome fragments in conditions when other homeologous chromosomes of the same group are present in the genome. Conclusions. Microsatellite loci specific to 5А, 5В, and 5D common wheat chromosomes can be used for identification of alien chromatin of chromosome 5T in the genome of amphidiploid.